Social Media Food Influencers and Follower’s Local Food Purchase Intention: A Parasocial Relationship Perspective - Rahmat Syarif; Kiki Reski Ramdhani Sucipto; Al Isra Denk Rimakka; Andi Ahmad Dzaki Maheza Pratama (Journal of Consumer Sciences, 2025)
Background: The presence of Social Media Food Influencers (SMFIs) has created a new landscape in local food tourism. Despite extensive studies focusing on the crucial role of influencer marketing through the lens of parasocial relationships, how SMFIs can foster these relationships and consequently influence their followers' intentions to purchase local food remains underexplored. Purpose: This research examines how the parasocial relationship between SMFIs and their followers influences the latter's intention to purchase local food. Method: This research employed the quantitative approach. It involved 439 active Instagram users who follow SMFIs as research respondents. They were recruited using the purposive sampling technique. Additionally, using Smart-PLS software, the Partial Least Squares Structural Equation Modeling (SEM-PLS) was applied to statistically test the data and the research hypotheses. Findings: This research reveals that influencers' content value (informative value), interaction strategy (interactivity), and credibility (expertise and attractiveness) positively and significantly influence the parasocial relationship between followers and social media food influencers (SMFIs). The results also indicate that this parasocial relationship influences followers' intention to purchase local food. Conclusion: This study highlights the critical role that food influencers play in fostering parasocial relationships, which significantly influence followers’ intentions to purchase local food. The findings reveal that the effectiveness of food influencers is largely contingent upon their ability to engage followers through informative content, interactive communication, and the establishment of perceived expertise. Research implication: The research findings offer significant implications for tourism marketers and local food business managers. Social media food influencers can be regarded as influential promoters of local food, enhancing tourists’ interest and purchase intentions through the parasocial relationships facilitated by social media.